Epidemiology and management of maxillofacial trauma caused by stabbing weapon at the University Hospital of Bouake (Côte d'Ivoire) - Éric Kouassi Zegbeh-N'guessan; Opokou Alexandre De Misère Ory; Ernest Martial Djemi; Pornan Issa Jules Berete (Elsevier, 2022)
Introduction: Injuries to the face caused by stabbing weapon are often severe and can constitute maxilla-facial emergencies. The aim of this study was to describe the epidemiological and clinical features and the difficulties in the management of these injuries caused by this trauma in a context of limited resources. Material and methods: This was a, retrospective and descriptive study that took place from 1 January 2018 to 31 December 2021 in the Odontostomatology and Maxillofacial Surgery Department of the University Hospital of Bouaké. It concerned patients admitted to the department for maxillofacial trauma caused by stabbing weapon. Results: 38 cases were collected. The average age was 32.96 years (extremes 19 and 48 years). The male gender predominated with a sex ratio of 8.5. All patients were victims of intentional assault with stabbing weapon. The weapon used was the machete in all cases. The injuries caused by this trauma were all complex, sometimes involving bone and organ damage. The jugal location predominated (34, 21%). The delay in treatment was most often more than 3 days. Discussion: The lesions caused by this trauma can be particular due to the complexity of the lesions caused. Their management is hampered by the economic difficulties of the patients and the lack of health infrastructure. Conclusion: The improvement of care will require the strengthening of infrastructural capacities and the establishment of an effective system to combat insecurity.